The effect of adding music during imagery training in enhancing the performance of Kelantan tenpin bowling players / Siti Nur Syafiqah Rosli - Rosli, Siti Nur Syafiqah (Faculty of Sport Science and Recreation, 2016)
Numerous studies found music has strong relationship with athletes' sporting performance. Thus, this study is conducted to determine the effectiveness of adding music during imagery training in enhancing the performance of Kelantan tenpin bowling player. Total of 14 subjects consists of 10 male and 4 female is selected for this study. Subjects were needed to listen to imagery training audio for 12 session and following with 1 week of washout period. Then, continued with imagery training audio adding with music for the same session. Subjects were required to perform pre and post-session of bowling shots before and after imagery training session. Results shows that there were significant difference between pre and post session of bowling shots for both imagery training (p < 0.05) where mean for imagery training with music is slightly higher rather than imagery training without music. Based on the result obtained, it can be concluded that in the present study, by adding music to the imagery training, the subjects' performance is greater.